2006
DOI: 10.1089/hum.2006.17.1241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oncolytic Herpesvirus NV1020 Can Be Enhanced by Combination with Chemotherapeutics in Colon Carcinoma Cells

Abstract: NV1020, an oncolytic herpes simplex virus type 1, can destroy colon cancer cells by selectively replicating within these cells, while sparing normal cells. NV1020 is currently under investigation in a clinical phase I/II trial as an agent for the treatment of colon cancer liver metastases, in combination with conventional chemotherapeutic agents such as 5-fluorouracil (5-FU), SN38 (the active metabolite of irinotecan), and oxaliplatin. To study the synergy of NV1020 and chemotherapy, cytotoxicity and viral rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…Specifically, 5-FU has been shown to increase viral replication in vitro and extend animal survival in vivo (33). In addition the additive and synergistic effect of combining HSV-1 oncolysis with 5-FU (rather than bioactivation of 5-FC) has been reported as well (34). Several studies have suggested that enhancement of viral replication by chemotherapeutics leading to increased cell death could be a possible explanation for the detected synergistic effects (3537).…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, 5-FU has been shown to increase viral replication in vitro and extend animal survival in vivo (33). In addition the additive and synergistic effect of combining HSV-1 oncolysis with 5-FU (rather than bioactivation of 5-FC) has been reported as well (34). Several studies have suggested that enhancement of viral replication by chemotherapeutics leading to increased cell death could be a possible explanation for the detected synergistic effects (3537).…”
Section: Discussionmentioning
confidence: 95%
“…These synergistic effects allowed for a dose reduction for both virus and drug without compromising cytotoxicity [100]. Other oncolytic HSV-1 strains have also shown enhanced cytotoxicity in combination with 5-FU [88, 119]. The HSV-1 oncolytic strain G207 has been shown to synergize with 5-FU resulting in a prolonged survival of mice with peritoneal dissemination of gallbladder cancer.…”
Section: Combination Therapy With Ovs and Drugs: More Than The Summentioning
confidence: 99%
“…While this does not always prove to be the case [39, 40], we hypothesized that the combination of RT and RT3D would result in an increase in viral replication, ultimately resulting in cell death. Our data clearly validated this hypothesis, with both one–step growth curves and plaque assays displaying a significant increase in viral replication with the addition of RT (Figure 3A, Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%